Clinician Descriptions of Communication Strategies to Improve Treatment Engagement by Racial/Ethnic Minorities in Mental Health Services: A Systematic Review - Aggarwal, Neil Krishan (Patient Educ Couns, 2015)
OBJECTIVE: To describe studies on clinician communication and the engagement of racial/ethnic minority patients in mental health treatment. METHODS: Authors conducted electronic searches of published and grey literature databases from inception to November 2014, forward citation analyses, and backward bibliographic sampling of included articles. Included studies reported original data on clinician communication strategies to improve minority treatment engagement, defined as initiating, participating, and continuing services. RESULTS: Twenty-three studies met inclusion criteria. Low treatment initiation and high treatment discontinuation were related to patient views that the mental health system did not address their understandings of illness, care or stigma. Treatment participation was based more on clinician language use, communication style, and discussions of patient-clinician differences. CONCLUSION: Clinicians may improve treatment initiation and continuation by incorporating patient views of illness into treatment and targeting stigma. Clinicians may improve treatment participation by using simple language, tailoring communication to patient preferences, discussing differences, and demonstrating positive affect. PRACTICE IMPLICATIONS: Lack of knowledge about the mental health system and somatic symptoms may delay treatment initiation. Discussions of clinician backgrounds, power, and communication style may improve treatment participation. Treatment continuation may improve if clinicians tailor communication and treatment plans congruent with patient expectations.